2022
DOI: 10.1590/fst.122821
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin on renal autophagy and interstitial fibrosis in diabetes mellitus

Abstract: To observe the effect of quercetin (Que) on renal autophagy level and renal interstitial fibrosis in the mice with diabetes mellitus (DM),and to discuss the possible mechanism. The wild-type C57BL/6 mice were randomly divided into 3 groups,including normal control (Normal) group, DM group and Que group (n = 9 in every groups). The diabetic mouse model was established by injection of streptozotocin. After 8 weeks of successful replication of the diabetic model,Que was given to the mice in Que group by continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Investigation on C57BL/KSJ db/db mice showed that quercetin attenuated podocyte apoptosis by inhibiting the EGFR signaling pathway [ 88 ]. In diabetic mice, quercetin ameliorates renal fibrosis by upregulating the autophagy level mediated by beclin-1 and downregulating snail1 expression [ 89 ].…”
Section: Bioactive Phytochemicals For Dnmentioning
confidence: 99%
“…Investigation on C57BL/KSJ db/db mice showed that quercetin attenuated podocyte apoptosis by inhibiting the EGFR signaling pathway [ 88 ]. In diabetic mice, quercetin ameliorates renal fibrosis by upregulating the autophagy level mediated by beclin-1 and downregulating snail1 expression [ 89 ].…”
Section: Bioactive Phytochemicals For Dnmentioning
confidence: 99%
“…Fibrosis was a pathological process in which cells were stimulated by chronic inflammation for a long time, resulting in the imbalance of extracellular matrix (extracellularmatrix, ECM) metabolism and collagen accumulation in tissues and organs, forming a large number of scar tissue, and then affecting the physiological function of diseased organs (Montesi et al, 2019;Wynn, 2008;Wynn & Ramalingam, 2012). Fibrotic diseases involved many organs of the body, such as lung, kidney, intestine, liver, etc., which posed a serious threat to human health (Wang et al, 2022;Chen et al, 2022). Therefore, slowing down or even blocking fibrosis had great clinical significance.…”
Section: Introductionmentioning
confidence: 99%